Crystal Structures and Thermal Properties of Two Transition-Metal Compounds {[Ni(DNI)(2)(H2O)(3)][Ni(DNI)(2) (H2O)(4)]}center dot 6H(2)O and Pb(DNI)(2)(H2O)(4) (DNI=2,4-Dinitroimidazolate) - Zhang, G.F.; Cai, M.Y.; Jing, P.; He, C.; Li, P.; Zhao, F.Q.; Li, J.Z.; Fan, X.Z.; Ng, S.W. (Kluwer (now part of Springer), 2010)
Two transition-metal compounds derived from 2,4-dinitroimidazole, {[Ni(DNI)(2)(H2O)(3)][Ni(DNI)(2)(H2O)(4)]}center dot 6H(2)O, 1, and Pb(DNI)(2)(H2O)(4), 2, were characterized by elemental analysis, FT-IR, TG-DSC and X-ray single-crystal diffraction analysis. Crystal data for 1: monoclinic, space group C2/c, a = 26.826(3), b = 7.7199(10), c = 18.579(2) angstrom, b = 111.241(2)degrees and Z = 4; 2: monoclinic, space group C2/c, a = 6.5347(6), b = 17.1727(17), c = 14.1011(14) angstrom, beta = 97.7248(10) and Z = 4. Compound 1 contains two isolated nickel centers in its structure, one being six-coordinate and another five-coordinate. The structure of 2 contains a lead (II) center surrounded by two chelating DNI ligands and four water molecules in distorted square-antiprism geometry. The abundant hydrogen bonds in two compounds link the molecules into three-dimensional network and stabilize the molecules. The TG-DSC analysis reveals that the first step is the loss of water molecules and the final residue is the corresponding metal oxides and carbon.